The challenges of cost control during the COVID-19 pandemic on the example of the company pro kolekt d.o.o - Martina Sopta Ćorić; Dino Rotter; Irijana Rajkovic (UTMS Journal of Economics, 2022)
The aim of the thesis Challenges of cost management during the COVID-19 pandemic on the example of the company Pro kolekt d.o.o. is to present an analysis of the report, focusing on cost management in the observed time period in 2019 and 2020. The analysis is focused on the current crisis caused by the virus pandemic that greatly affected the company's operations and sought rapid adjustment of cost management to keep the company going in the new crisis. The subject of the thesis is to present the application of cost management theory in a crisis situation. The paper provides a detailed insight into the importance of timely response of managers in a crisis situation in which the company finds itself in order to preserve its business and survive in the market in the new conditions. In the first part, a theoretical framework for managing the operating costs of a modern company in the financial industry is set. Afterwards, crisis cost management is presented, with a look at the current crisis caused by the pandemic. In the last part, the analysis refers to the financial sustainability of the company's operations in the observed period, with proposals and other options for setting strategic plans and goals of the company in the future. The main goals of the thesis are: • to analyze available data on the development and changes during the virus pandemic • to collect and analyze available secondary data indicating changes in cost management • to explore the opinions of the company's managers on the success of the adjustment and the future of the company. In preparing this paper, secondary data collected from the professional literature will be used in order to lay the foundations for the analysis of cost management in the real sector during a pandemic. Secondary data will be processed by methods of analysis, comparison and synthesis.
Keywords: F01; Z32; 330; Pro collection; cost management; crisis; pandemic; covid-19